Effect of swim intensity on responses to dynamic apnoea - Guimard, KA.; Collomp, K.; Zorgati, H.; Brulaire, S.; Woorons, X.; Amiot, V.; Prieur, F. (Journal of Sports Sciences, 2018)
The aim of this study was to determine the influence of swim intensity on acute responses to dynamic apnoea. 9 swimmers performed one 50 m front crawl trial in four different conditions: at 400 m velocity (V400) with normal breathing (NB), at V400 in complete apnoea (Ap), at maximal velocity (Vmax) with NB and at Vmax in Ap. Peak heart rate (HRpeak), blood lactate concentration after exercise (Lacpost ex) and Borg rating of perceived exertion (RPE) were measured. Arterial oxygen saturation (SpO2) was monitored with a pulse oximeter at forehead level during and after exercise. In Ap, swimming at V400 induced a significantly lower HRpeak and Lacpost ex than swimming at Vmax whilst RPE and the kinetics of SpO2 were not different at V400 and at Vmax. The minimal value of SpO2 in Ap was reached 10 to 11 s after the end of V400 and Vmax (81.7 ± 10.1% and 84.4 ± 10.6%, respectively). Swimming a 50 m front crawl in Ap resulted in a large decrease in SpO2 which occurred only after the cessation of exercise. The higher duration of apnoea during submaximal exercise could explain why SpO2 and RPE reached the same values as for maximal exercise.?